Efectos cardiovasculares del extracto acuoso de las hojas de Clusia coclensis (Guttiferae) - García González, Mildred (Universidad de Costa Rica, 1996)
Aqueous extracts of the leaves of Clusía coclensís, (Guttiferae) injected intravenously to 42 normal Sprague- Dawley rats and to 42 Spontaneous Hypertensive rats, in 7 different doses, induced a rapid and transitory decrease in blood pressure and heart frequency. The magnitude of blood pressure decrease was dose-dependent. The effect was statistically significant (p S 0.0l), probably due to sympathetic stimuli